2019
DOI: 10.1111/nph.15836
|View full text |Cite
|
Sign up to set email alerts
|

The WY domain in the Phytophthora effector PSR1 is required for infection and RNA silencing suppression activity

Abstract: Summary Phytophthora pathogens manipulate host innate immunity by secreting numerous RxLR effectors, thereby facilitating pathogen colonization. Predicted single and tandem repeats of WY domains are the most prominent C‐terminal motifs conserved across the Phytophthora RxLR superfamily. However, the functions of individual WY domains in effectors remain poorly understood. The Phytophthora sojae effector PSR1 promotes infection by suppressing small RNA biogenesis in plant hosts. We identified one single WY do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Gene-specific primers were designed using Primer Premier 5.0 (Table S1). Then, quantitative PCR (qPCR) was carried out using Maxima SYBR Green/ROX qPCR Master Mix (Zhang et al, 2019;Chen et al, 2020). The EF-1a gene was used as an internal reference.…”
Section: Rna Extraction and Quantitative Real-time Pcr (Qrt-pcr) Analmentioning
confidence: 99%
“…Gene-specific primers were designed using Primer Premier 5.0 (Table S1). Then, quantitative PCR (qPCR) was carried out using Maxima SYBR Green/ROX qPCR Master Mix (Zhang et al, 2019;Chen et al, 2020). The EF-1a gene was used as an internal reference.…”
Section: Rna Extraction and Quantitative Real-time Pcr (Qrt-pcr) Analmentioning
confidence: 99%
“…Samples were analyzed by qRT-PCR as described previously (Zhang et al, 2019;Xu et al, 2020). Briefly, 1 µg of total RNA was reverse transcribed using the TransScript II One-Step gDNA Removal and cDNA Synthesis SuperMix (TransGen Biotech).…”
Section: Expression Analysis Of Mirnas and Their Targets By Qrt-pcr Amentioning
confidence: 99%
“…Functional studies of WY domain containing proteins have indicated that certain residues in the WY domain are essential for the immune suppressing functions of P. sojae effectors Avr1b [32] and PSR1 [33], and P. infestans effectors Avr3a [34] and PexRD2 [35]. Furthermore, mutation of two conserved leucines in the WY domain of PexRD2 disrupted interaction with its target, MAPKKKε, consistent with this domain being important for protein-protein interactions [35].…”
Section: Introductionmentioning
confidence: 99%